Principles of anthropocentrism in Modern Linguistics: Linguistic personality - Ayna Rakhimova, Arailym Amanzholova, Jakypbekova Mamilya,; Smagulova, Guldarkhan N.; Kalamkas, Kalybayeva (Opción, 2019)
The study aims to investigate the principles of anthropocentrism in modern linguistics via a comparative qualitative research method. As a result, the linguistic personality is a concept that can be translated into a specific category of linguistic spheres, which has not been defined in terms of concrete, conclusive concept. In conclusion, in order to discover the mentioned scientific categories, it is necessary to analyze the aforementioned influencing factors, the scientific aspects are taken by the object and defining levels through experiment.